AFFIRMING THE LINK BETWEEN WORKERS’ SAFETY BEHAVIOR AND ORGANISATIONAL SAFETY PERFORMANCE OF SME MANUFACTURING (Social Security Management Journal, 2024)
In the Malaysian context, small and medium enterprises (SMEs) encountered workplace accidents. Scholarly consensus attributes a substantial portion of these accidents and injuries to the human factor, specifically unsafe behaviours. This study, conducted in Malaysia’s northern region, focused on Safety and Health/Human Resource professionals within the manufacturing sector of SMEs. We compiled a robust dataset comprising 107 responses garnered through a meticulously designed self-administered questionnaire. To scrutinise the intricate relationship between safety behaviour and safety performance, we subjected the data to rigorous analysis using SmartPLS 3.2.9, employing advanced partial least square–structural equation modelling (PLS-SEM) techniques. The research outcomes unequivocally underscore the palpable and consequential impact of safety behaviour variables, namely safety compliance and safety participation, on improving safety performance, gauged through parameters such as accidents, injuries, and property damages. These results resoundingly validate the research hypotheses. Consequently, this study accentuates the importance of cultivating employee safety behaviour, particularly in resource-constrained SME settings, as an imperative step toward enhancing workplace safety.